Long-legged flies (Diptera: Dolichopodidae) in the collection of the Natal Museum: A review of C.H. Currans types, new synonyms, and new combinations - Grichanov, Igor Ya.; Mostovski, Mike B. (Zootaxa, 2009)
C.H. Curran’s Dolichopodidae types in the collection of the Natal Museum are reviewed. Campsicnemoides Curran, 1927, is placed here in synonymy to Acropsilus Mik, 1878 (syn. nov.; male holotype of Campsicnemoides vorax Curran, 1927, has been examined in the collection of NMSA, redescribed and illustrated, and a new combination is here proposed, Acropsilus vorax (Curran, 1927), comb. nov.). The following recombinations are also proposed (comb. nov.): Trigonocera munroi (Curran, 1926c) [Diaphorus], Micromorphus aristalis (Curran, 1926a) [Sympycnus], Peloropeodes niger (Curran, 1926a) [Sympycnus]. The following synonyms are proposed in this paper (syn. nov.): Sympycnus discrepans Parent, 1934, S. rusticus Parent, 1935, and S. allotarsis Meuffels & Grootaert, 2007, are placed in synonymy to Sympycnus basilaris (Curran, 1924); Diaphorus inversus Curran, 1924, is placed in synonymy to Diaphorus dasycnemus Loew, 1858; Medetera longitarsis Curran, 1924, and M. afra Curran, 1927, are placed in synonymy with Medetera simplicis Curran, 1924.